A fool's game: Blood doping in sport - Towns, C. R.; Gerrard, D. F. (Performance Enhancement & Health, 2014)
`Blood doping` involves the transfusion of blood into an athlete's circulation to boost their oxygen carrying capacity. The procedure has been used in endurance events such as cycling and skiing but is prohibited by the World Anti-Doping Agency. The validity of restrictions on performance enhancement including `blood doping` has been challenged. However, the argument for legalisation fails to recognise the significant risks inherent to the use of blood products that include: immune reaction, bacterial contamination and the transmission of viral disease. The argument also fails to recognise the disparities in health resources that would render athletes from less wealthy nations at much greater risk. There are significant, health risks associated with blood doping; this seriously compromises claims for legalisation.